Recognize the valuable role of athletic trainers. Issue 9 (December 2014) - Neal, Timothy; Quandt, Eric; Thornton, James; Anderson, Jeffrey
<x xml:space="preserve">Abstract</x> The competitive nature of intercollegiate athletics is an alluring feature for fans, alumni and the media. This places great pressure for success on athletics departments, coaches and student‐athletes. This pressure may even extend into the medical care and well‐being of student‐athletes. The competitive nature of coaches and student‐athletes may color their reactions to medical decisions made by sports medicine staff members and team physicians, who base their decisions on the long‐term well‐being of the student‐athletes.